PORTLAND CEMENT CONCRETE FOR ANTARCTICA. - Keeton,John R. (1970)
A satisfactory concrete mix was developed in the Naval Civil Engineering Laboratory for use in Antarctica. This mix was subsequently utilized at McMurdo Station, Antarctica, during Deep Freeze 1969 to construct simulated footings and slabs. Techniques were developed in the field which led to formulation of recommended procedures for batching, mixing, placing, and curing of portland cement concrete in Antarctica. The pertinent features of the mix and design and related procedures are given. (Author)